Increased abundance of myeloid-derived suppressor cells and Th17 cells in peripheral blood of newly-diagnosed Parkinson's disease patients. (1st May 2017) - Chen, Siyuan; Liu, Yueqin; Niu, Yuanyuan; Xu, Yuhao; Zhou, Qianwen; Xu, Xiujian; Wang, Jia; Yu, Ming
Highlights: For the first time, increased levels of MDSCs were measured in early stage PD. This highlights the role of Th17 cells and MDSCs in the neuroinflammatory response. Foundation for elucidating interactions between MDSCs and Th17 cells in PD was laid. Abstract: Parkinson's disease (PD) is a neurodegenerative disease that is often associated with corresponding neuroinflammation. In the present study, flow cytometry was used to detect T-helper 17 (Th17) cells and myeloid-derived suppressor cells (MDSCs) in 18 patients newly diagnosed with PD as well as 18 normal controls. Results showed that Th17 cells and MDSCs were significantly higher in peripheral blood of PD patients compared to controls ( P <  0.001). Furthermore, there was no correlation between Th17 cells and MDSCs in peripheral blood of PD patients. Our findings suggest that Th17 cells and MDSCs may be important factors related to the occurrence and progression of PD, as well as the development of PD-related neuroinflammation.